Pemanfaatan Pojok Literasi Arkeologi (PLA) dalam Meningkatkan Minat Belajar Sejarah Peserta Didik di SMA Negeri 14 Semarang - Sholikhah, Khaditsa Ni'matus; Amin, Syaiful (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyze the effectiveness of the Archaeologival Literacy Corner as an innovative learning resource in enhancing student’s interest in and awareness of history. The primacy focus of the study is to evaluate the transformation of passive literacy into exploratory activites through direct interaction with archaeological artifacts in the classroom. The research method employed is descriptive qualitative. Data collection was conducted through participatory observation, in-depth interviews with teacher and students, and a review a documentation regrading the use of artifacts as intructional media. Data analysis was carried out using techniques of data reduction, data presentation, and inductive reasoning to obtain a comprehensive picture of the dynamics of the learning environment. The research findings indicate that the availability of relevant and authentic learning resources is capable of maintaining students learning motivation consistenly. Intellectual esperiences involving the routine handling, observation, and evaluation of archaelogical sources have been shown to transform student’s perceptions of history lessons froma a boring activity into an engaging intellectual journey. The conclusion of this study is that schools serve a strategic role as centers of the dissemination of knowledge and the development of historical awareness through the integration of real artifacts and local knowledge. The consistent use of archaeological literacy tools helps students explore their national identity and sretngthen their emotional connection.